Preventive deformation measurements on cultural heritage materials based on non-contact surface response of model samples. (August 2015) - Tornari, Vivi; Bernikola, Eirini; Tsigarida, Nota; Andrianakis, Michalis; Hatzigiannakis, Kostas; Leissner, Johanna
Abstract : Due to climate change a slowly increasing annual temperature may be experienced by structures. Relative humidity (RH) fluctuations affect the equiibrium moisture content of materials. Repeated RH cycling leads to mechanical failure and may endanger an object's structural integrity. Preventive conservation is based on adopting measures that will prevent fracture. Real-time interferometry allows the acquisition of sequential high-resolution full-field surface images from hygroscopic materials used in cultural heritage by recording during cycles of changing RH. The differential images allow the development of a preventive methodology directly through surface responses. Indications of the natural onset of degradation can be followed and traced before visible damage occurs, allowing preventive measures to be taken in advance. An ongoing study (Climate for Culture European project (FP7-ENV-2008-1 CfC no. 226973)) aims to experimentally classify structural deterioration as a function of acclimatization and confirm the hypothesis that surface responses before deformation can indicate deformation threshold values as reference points for the onset of RH-induced deterioration.